2022
DOI: 10.1002/cjas.1666
|View full text |Cite
|
Sign up to set email alerts
|

The impact of state fragility on FDI inflows: The moderating role of natural resources and democratic governance in the MENA region

Abstract: The main contribution of this study to international business research is to integrate state fragility as a multidimensional factor determining FDI inflows. After considering 17 countries in the MENA region for the period between 2002 and 2018, our results reveal that state fragility has a negative impact on inward FDI. However, this negative relationship turns out to be moderated by natural resource endowment and democratic governance. While lower levels of democratic governance strengthen the negative impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
2
1
0
Order By: Relevance
“…Finally, the study discovers that government effectiveness stimulates regional growth while decreasing the positive effect of natural resource endowment on economic growth, whereas regulatory quality increases the positive effect of natural resource endowment on economic growth. The above findings are in agreement with the study of Triki et al (2022) who found a resource curse phenomenon in the MENA region. In contrast, using daily data between January 1, 2019, to July 1, 2021, Sun and Wang (2021) investigated the relationship between natural resource commodity price volatility and global economic performance.…”
Section: Literature Reviewsupporting
confidence: 93%
“…Finally, the study discovers that government effectiveness stimulates regional growth while decreasing the positive effect of natural resource endowment on economic growth, whereas regulatory quality increases the positive effect of natural resource endowment on economic growth. The above findings are in agreement with the study of Triki et al (2022) who found a resource curse phenomenon in the MENA region. In contrast, using daily data between January 1, 2019, to July 1, 2021, Sun and Wang (2021) investigated the relationship between natural resource commodity price volatility and global economic performance.…”
Section: Literature Reviewsupporting
confidence: 93%
“…This finding rejects the second hypothesis. The insignificant but positive relationship between the said variables is verified from similar findings of some important studies [7,10,11,18,25,29,30,32]. The possible interpretation for this insignificant relationship between trade openness and "FDI inflow" in "middle-income" economies is that the trade openness does not potentially contribute to enhancing the foreign investor's confidence in making their investment in the host country in "middle-income" economies.…”
Section: Empirical Analysissupporting
confidence: 73%
“…The past literature provides a large number of evidence in support of a positive and highly significant relationship between trade openness and "FDI inflow" in different regions of the world using time series, as well using aggregate panels of different economies such as in [11], which uses a comparative panel of developed and developing countries; [29] in the case of post-communist economies; [7] in the case of Pakistan; [10] for a panel of selected ASEAN countries; [18] in the case of a selected panel from Caribbean countries; [30] in the case of India; [31] in the case of India again; and, finally [32] in the case of some countries from the MENA region. However, some important studies still provided the insignificant yet positive impact of trade openness on "FDI inflow" for individual countries as well as on some panel studies such as [12] in the case of Africa; [33] for a panel of emerging markets; [34] in the case of developing and emerging countries; [35] in the case of Saudi Arabia; and [36] in the case of some of the MENA countries.…”
Section: Literature Reviewmentioning
confidence: 99%